2017
DOI: 10.1186/s12874-017-0440-3
|View full text |Cite
|
Sign up to set email alerts
|

Using Mechanical Turk to recruit participants for internet intervention research: experience from recruitment for four trials targeting hazardous alcohol consumption

Abstract: BackgroundMechanical Turk (MTurk) is an online portal operated by Amazon where ‘requesters’ (individuals or businesses) can submit jobs for ‘workers.’ MTurk is used extensively by academics as a quick and cheap means of collecting questionnaire data, including information on alcohol consumption, from a diverse sample of participants. We tested the feasibility of recruiting for alcohol Internet intervention trials through MTurk.MethodsParticipants, 18 years or older, who drank at least weekly were recruited for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 23 publications
2
41
0
Order By: Relevance
“…Our study further extends findings by Kok et al who assessed attribute preferences amongst patients who had previously underwent an elective coronary procedure . In this study, the majority of participants preferred same‐day discharge to overnight stay.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Our study further extends findings by Kok et al who assessed attribute preferences amongst patients who had previously underwent an elective coronary procedure . In this study, the majority of participants preferred same‐day discharge to overnight stay.…”
Section: Discussionsupporting
confidence: 87%
“…Our study further extends findings by Kok et al who assessed attribute preferences amongst patients who had previously underwent an elective coronary procedure. 19 In this study, the majority of participants preferred same-day discharge to overnight stay. Interestingly, Kok et al found that about half of their respondents viewed an overnight stay as more desirable than same-day discharge.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Third, we used inclusion criteria of 95% approval rates and 100 or more previous mTurk tasks that could have increased the reliability of our group of participants and inflated some findings (e.g., response rates). Restricting participants based on approval rates and/or previous tasks completed is common in mTurk studies (e.g., Cunningham et al, ; Reed et al, ; Strickland & Stoops, ). Previous research has shown that these restrictions can improve data quality (e.g., participants are less likely to demonstrate central‐tendency biases or fail attention checks) as well as result in lower rates of socially desirable responding (Peer, Vosgerau, & Acquisti, ).…”
Section: Discussionmentioning
confidence: 99%
“…Participants were recruited from mTurk. In order to view the study, participants were required to have an approval rating of 95% or higher on previous tasks, have completed at least 100 mTurk tasks, and currently reside in the United States, consistent with other research (e.g., Cunningham, Godinho, & Kushnir, ; Reed, Becirevic, Atchley, Kaplan, & Liese, ; Strickland & Stoops, ). A short (~1 min) screening survey, including demographic and alcohol use questions, was used to determine study eligibility.…”
Section: Methodsmentioning
confidence: 99%